PEMBELAJARAN KESASTRAAN ARAB ( PUISI DAN PROSA) DI MTS UNWANUL FALAH SOLJER - Moch Cecep Abdul Azis (Arabic Language and Education, 2025)
This research aims to discuss literature learning with a study focus on Arabic poetry and prose. This research uses a library approach by reviewing several credible literature with data sources from scientific articles, observations, interviews with related parties and documentation. The results of this research show that there are three levels in literature learning, namely Basic Level (Mubtadi'), Intermediate Level ( Mutawassith), and Advanced Level (Mutaqaddim). The learning methods used in learning syi'r and Arabic prose at MTS Unwanul Falah include the reading method. The reading method is to present lesson material by prioritizing reading, namely the teacher first reads the reading topics, then the students follow. Keywords : Learning, Arabic literature, Prose, Poetry